Bertolt Brecht: His Life, His Art, His Times - Ewen, Frederic (New York Carol Publishing Group, 1992)
Highly acclaimed when it was first published in 1967, Frederic Ewen's monumental biographical study of Bertolt Brecht has long been out of print. In response to national demand, Citadel Press is proud to reissue this complete and unabridged text.Of "Bertolt Brecht: His Life, His Art, His Times, the critics wrote:"The finest critical study of Brecht to date. This book is at least a worthy appreciation of a towering, poetic and dramatic genius." -Los Angeles Times"What is particularly striking about Frederic Ewen's biography is that it conveys the excitement, the turmoil and triumph of Brecht's career." -The New York Times"The great thing about Frederic Ewen's luminous biography is that it gently frees Brecht from the bear hugs of the bigots and restores him to us as a whole man, his youth contained in his age." -The Nation